The Motion of a Neutrally Buoyant Ellipsoid Inside Square Tube Flows (Advances in Applied Mathematics and Mechanics, 2018)
The motion and rotation of an ellipsoidal particle inside square tubes andrectangular tubes with the confinement ratio $R/a$∈(1.0,4.0) are studied by the latticeBoltzmann method (LBM), where $R$ and $a$ are the radius of the tube and the semi-majoraxis length of the ellipsoid, respectively. The Reynolds numbers ($Re$) up to 50 areconsidered. For the prolate ellipsoid inside square and rectangular tubes, three typicalstable motion modes which depend on $R/a$ are identified, namely, the kayaking mode,the tumbling mode, and the log-rolling mode are identified for the prolate spheroid.The diagonal plane strongly attracts the particle in square tubes with 1.2 ≤ $R/a$